Economic impact of typhoon-induced wind disasters on port operations: A case study of ports in China. (November 2020) - Zhang, Yi; Wei, Kai; Shen, Zhonghui; Bai, Xiwen; Lu, Xinzheng; Soares, Carlos Guedes
Abstract: The impact of a port disruption can reverberate across the entire economy through global supply chains. It is essential to ensure the regular operation of seaborne transportation considering all risks. Climate events create challenging risks that need to be carefully addressed. This paper proposes an approach to evaluate the economic losses due to port disruptions caused by typhoon-induced wind disasters. Four Chinese ports and their historical typhoon and cargo throughput data from 2007 to 2017 are taken as examples. A wind model is introduced to analyze the wind fields of typhoons. The likelihood of port disruption is then estimated based on the simulated wind field results at each port. Based on the estimated number of port disruption days and daily cargo throughput, the total economic loss of each port is calculated by considering the reputational loss, loss to the shippers, loss to the carriers, and loss to the ports. Finally, the economic impact of port disruption caused by the typhoon-induced wind disasters on port operations in China is discussed. The results suggest that both the disruption time and throughput are critical in economic estimations and the major component of the overall cost is the loss to the shippers. The proposed method directly reflects the typhoon-induced wind disaster-related risks quantitatively encountered at ports, which could help port managers make optimal decisions in controlling port operations.